Tetraspanins and Mouse Oocyte Microvilli Related to Fertilizing Ability. (July 2017) - Benammar, Achraf; Ziyyat, Ahmed; Lefèvre, Brigitte; Wolf, Jean-Philippe
Our electron microscopy observations demonstrate for the first time that the number of microvilli on the mice oocyte membrane decreases when meiosis progresses from prophase I to metaphase II (MII) stage, and the morphology of the microvilli also changes. Microvilli are significantly shorter and larger on the ovulated oocyte membrane than at the previous stages. Although clathrin vesicles clearly disappear during oocyte maturation, exosome-like vesicles begin to be secreted at the metaphase I stage, more strongly at the MII stage. Multivesicular bodies are visible only at the MII stage. Since several oocyte tetraspanins are involved in the gamete interaction, Cd9 being congregated on the MII oocyte microvilli, we analyzed the effect of tetraspanin deletion on oocyte membrane morphology. The Cd9 −/− and Cd9 −/− Cd81 −/− deletions are associated with a decreased microvilli density on the MII oocyte surface. Microvilli thickness is significantly increased whatever the deleted tetraspanin gene be. Only Cd9 deletion clearly disturbs the vesicular traffic, increasing the number of clathrin and exosome vesicles. Additional investigations are necessary to elucidate how tetraspanins modulate the microvilli morphology, likely in relation with cytoskeleton. The role of oocyte exosomes in gamete adhesion/fusion remains to be further studied.